To Post or Not to Post: Plastic Surgery Practice Marketing, Websites, and Social Media?. Issue 7 (July 2019) - Mess, Sarah A.; Bharti, Gaurav; Newcott, Ben; Chaffin, Abigail E.; Van Natta, Bruce W.; Momeni, Reza; Swanson, Scott
Abstract : Summary: Social media is beginning to eclipse practice websites and other traditional electronic marketing utilized by plastic surgeons. First, highlights are presented from the relevant electronic marketing literature. Next, this article presents a new case study of how, why, when, and what social media is being used by ASPS members (n = 100). Results suggest a significant disconnect between plastic surgeons and the highest impact platforms reported in the literature such as Instagram, YouTube, Snapchat, and Facebook. Plastic surgeons currently prefer to focus electronic marketing efforts on practice websites over social media platforms. This study suggests that instead of relying on their practice websites to disseminate information, surgeons should be utilizing social media, posting promotions, before-and-after photos, and videos to develop their client base.